SHP2 inhibition by SHP099 attenuates IL-6–driven osteoclastogenesis in growth plate injury - Zhang, Qin; Li, Ning; Dai, Zhen-Zhen; Liu, Xiao-Man; Ding, Jing; Sha, Lin; Li, Hai (Frontiers in Immunology, 2025)
IntroductionDisruption of growth plate cartilage often leads to severe bone growth defects in children, necessitating novel therapeutic strategies. Following growth plate injury, an inflammatory response is rapidly initiated, resulting in the release of pro-inflammatory cytokines such as IL-6 into the injured tissue, which subsequently induce and enhance osteoclast generation and differentiation. This study investigates the role of SHP2 in regulating IL-6-driven osteoclastogenesis during growth plate injury repair.MethodsTibial drill-hole injuries were induced in C57BL/6 mice (n=9), with SHP099 (30 mg/kg, intra-articular) administered to intervention groups and tissues were harvested for qPCR/histology. RAW 264.7 cells were treated with RANKL (100 ng/ml) ± IL-6 (100 ng/ml) ± SHP099 (15 µM). Osteoclast differentiation, expression level of pro-inflammatory cytokines and the associated signaling pathway were assessed via TRAP staining, Western blot, qPCR and ELISA. ResultsSHP2/PTPN11, osteoclast markers (CTSK/OSCAR) and pro-inflammatory cytokines (IL-6, IL-1β, TNF-α) was upregulated and could be inhibited by SHP099 at injury sites. IL-6 enhanced p-SHP2/p-TAK1 expression, osteoclastogenesis and inflammatory response in vitro, while SHP099 effectively reduced osteoclast numbers, downregulating CTSK/OSCAR and pro-inflammatory cytokines (IL-6, IL-1β, TNF-α). Furthermore, the NF-κB pathway remained unaffected by SHP099, indicating a distinct signaling mechanism through which SHP2 regulates osteoclastogenesis. DiscussionOur findings underscore the pivotal role of SHP2 as a downstream signaling molecule of IL-6 in mediating inflammatory responses during bone repair, suggesting that SHP2 inhibition may present a novel therapeutic approach to prevent pathological bone remodeling and enhance recovery following growth plate injuries. Future investigations should focus on the translational potential of SHP2 inhibitors in pediatric orthopedics.